Séroprevalence Anaplasma phagocytophilum u pacientů se suspektní lymeskou borreliózou - Dvořáková Heroldová, M; Dvořáčková, M (Epidemiologie, mikrobiologie, imunologie, 2014)
Human granulocytic anaplasmosis (HGA) is an emerging tick-borne zoonotic disease caused by an obligate intracellular bacterium, Anaplasma phagocytophilum. In Europe, A. phagocytophilum is transmitted by Ixodes ricinus ticks. After Lyme borreliosis and European tick-borne encephalitis, HGA is the third most common tick-borne infection in the USA and Europe. The clinical symptoms of anaplasmosis are non-specific and include malaise, fever, headache, myalgia, and arthralgia. In more severe cases, the gastrointestinal or respiratory tract may be affected. However, most infections are asymptomatic. The aim of our study was to determine the seroprevalence of A. phagocytophilum in patients with suspected Lyme borreliosis. A total of 314 sera from patients with suspected Lyme borreliosis were screened for IgG and IgM antibodies against A. phagocytophilum. The immunoblot assay was used to detect the antibodies. Anti-A. phagocytophilum antibodies were detected in 34 patients, i.e. in 10.82%. IgM antibodies were positive in 19 cases and IgG antibodies in 10 cases. Positivity to both IgM and IgG antibodies was revealed in five patients. Antibodies against Borrelia burgdorferi sensu lato were detected in 181 patients (57.64%). Co-seroprevalence of Borrelia burgdorferi s. l. and A. phagocytophilum was found in 26 patients (8.3%). Positivity for anti-A. phagocytophilum antibodies was most often seen in samples from the age group 60-69 years. Our results show that A. phagocytophilum infection is not uncommon in the Czech Republic and should be considered in patients with a history of a tick bite.
Keywords: protilátky bakteriální; lymeská nemoc; dospělí; Animals; anaplasmóza; Female; Borrelia burgdorferi; Adult; ženské pohlaví; lidé; Aged, 80 and over; Antibodies, Bacterial; klíšťata; Ticks; séroepidemiologické studie; Male; Aged; Czech Republic; Seroepidemiologic Studies; Lyme Disease; Anaplasma phagocytophilum; Anaplasmosis; Česká republika; lidé středního věku; senioři nad 80 let; senioři; zvířata; mužské pohlaví; Middle Aged; Humans